A dual colorimetric chemosensor for Hg(ii) and cyanide ions in aqueous media based on a nitrobenzoxadiazole (NBD)–antipyrine conjugate with INHIBIT logic gate behaviour. Issue 37 (15th September 2020) - Anand, Thangaraj; Sankar, Muniappan
Abstract : Chemosensor 1 was synthesized by an elegant method and utilized for dual detection of Hg(ii ) and CN − ions in aqueous media. Abstract : In this work, we have synthesized nitrobenzoxadiazole–antipyrine conjugate 1 from chloro substituted nitrobenzoxadiazole (NBD) with 4-aminoantipyrine by an elegant method which provides good yield and it is characterized by various spectroscopic techniques. The sensing ability of compound 1 is analyzed with the addition of different metal ions and anions in an aqueous methanol medium. It shows rapid colorimetric response for Hg 2+ and CN − ions over a wide range of competitive metal ions and anions. On addition of Hg 2+ /CN − ions, 1 shows a distinct color change from pale yellow to pink and orange red, respectively, thus permitting chemosensor 1 to be used for 'naked eye' detection of Hg 2+ and CN − ions. The change in spectral features and color of 1 with the addition of Hg 2+ and CN − ions is mainly due to the formation of a charge-transfer complex (1 2 –Hg 2+ ) and cyanide ion induced deprotonation of 1 . The interaction between the Hg 2+ /CN − ion and 1 is characterized by mass spectrometry and 1 H-NMR spectral titrations. In addition, sensor 1 is reversible and reusable and it can be developed as an INHIBIT type logic gate. Compound 1 detects Hg 2+ and CN − ions upto 2.57 × 10 −8 M and 1.67 × 10 −7 M, respectively. Further, compound 1 pre-coated test strips detect Hg 2+ and CN − ions and they provide a simple and convenient method for determination of Hg 2+ /CN − ions.